β-glucan Exposure on the Fungal Cell Wall Tightly Correlates with Competitive Fitness of Candida Species in the Mouse Gastrointestinal Tract - Sem, XiaoHui; Le, Giang T. T.; Tan, Alrina S. M.; Tso, Gloria; Yurieva, Marina; Liao, Webber W. P.; Lum, Josephine; Srinivasan, Kandhadayar G.; Poidinger, Michael; Zolezzi, Francesca; Pavelka, Norman (Frontiers in Cellular and Infection Microbiology, 2016)
Candida albicans is responsible for ~400,000 systemic fungal infections annually, with an associated mortality rate of 46–75%. The human gastrointestinal (GI) tract represents the largest natural reservoir of Candida species and is a major source of systemic fungal infections. However, the factors that control GI colonization by Candida species are not completely understood. We hypothesized that the fungal cell wall would play an important role in determining the competitive fitness of Candida species in the mammalian GI tract. To test this hypothesis, we generated a systematic collection of isogenic C. albicans cell wall mutants and measured their fitness in the mouse GI tract via quantitative competition assays. Whereas a large variation in competitive fitness was found among mutants, no correlation was observed between GI fitness and total levels of individual cell wall components. Similar results were obtained in a set of distantly-related Candida species, suggesting that total amounts of individual cell wall components do not determine the ability of fungi to colonize the GI tract. We then subjected this collection of Candida strains and species to an extensive quantitative phenotypic profiling in search for features that might be responsible for their differences in GI fitness, but found no association with the ability to grow in GI-mimicking and stressful environments or with in vitro and in vivo virulence. The most significant association with GI fitness was found to be the strength of signaling through the Dectin-1 receptor. Using a quantitative assay to measure the amount of exposed β-glucan on the surface of fungal cells, we found this parameter, unlike total β-glucan levels, to be strongly predictive of competitive fitness in the mouse GI tract. These data suggest that fungal cell wall architecture, more so than its crude composition, critically determines the ability of fungi to colonize the mammalian GI tract. In particular, recognition of exposed β-glucan by Dectin-1 receptor appears to severely limit Candida GI fitness and hence represents a promising target to reduce fungal colonization in patients at risks of systemic candidiasis.